STRENGTHENING NATIONAL IDENTITY THROUGH TOUR EDUCATION PURBAKALA CIPARI KUNINGAN ARCHAELOGICAL SITE - Priantia, Ayu Yuliana (Universitas Pendidikan Indonesia, 2017)
Abstract-This globalization era demands the society to be competitive. The society should be able to compete with other countries in the world. The development of science and technology become the keys in facing the gate of the big world. The access of practicality and freedom become the offerings which are inseparable from the societyâ€™s life. This study is aimed to strengthen national identity through tour education Purbakala Cipari archaeological site in Kuningan regency. Through tour education which contains historical and cultural values, it will lead the citizen to understand their identity as Indonesian which holds unity in the high self esteem. Â The study used qualitative as the approach and descriptive as the methodology. The data was obtained through observation, interview, documentation study and literature review. The research procedures were deciding the types of data, sources of the data, data collection procedure and data analysis technique. The result of the study showed Pubakala Cipari archaeological site has cultures depicted by prehistory objects and the values on them which appropriate with citizenâ€™s identity, especially Indonesian. The general conclusion which can be taken from the study is Purbakala Cipari has been contributed in facilitating an education field for the society and as an inheritance of prehistory it has a big role in strengthening national identity.Keywords: National identity, Tour Education, Purbakala Cipari archaeological site